Facial-submental island flap for reconstruction of hemitongue defects in young, middle-aged and elderly patients with early and middle stage oral tongue squamous cell carcinoma - Yan Wang; Bin Zhou; Wei-liang Chen; Zi-xian Huang; Rui Chen (Head & Face Medicine, 2022)
Abstract Background This study evaluated the outcomes of facial-submental artery island flap (FSAIF) for reconstruction of the hemitongue following cancer ablation in patients with early and middle-stage oral tongue squamous cell carcinoma (OTSCC). Methods In total, 122 patients with early and middle-stage OTSCC were divided into young, middle-aged, and elderly groups. The Adult Comorbidity Evaluation-27 (ACE-27) index was used to determine the presence of comorbidities. The patients underwent surgical treatment with hemiglossectomy, neck dissection, and hemitongue reconstruction using FSAIF. In addition, stage I (n = 15) and II (n = 69) patients underwent ipsilateral selective neck dissection, whereas those with stage III (n = 38) underwent radical neck dissection. Six patients with T3N1 disease also underwent cobalt-60 adjuvant radiotherapy. Results Young and elderly patients exhibited significant differences in comorbidities, as assessed by the ACE-27 (p < .05). The skin paddles in the young, middle-aged, and elderly patients were 3 × 9 to 4 × 12 cm, 3 × 11 to 4 × 12, and 3 ×  10 to 5 × 13 cm in size, respectively. FSAIF failure occurred in four patients (success rate: 96.7%). No significant differences were observed in the skin paddle of the flap or rate of flap failure among the age groups (p > .05). Clavien-Dindo grades I, II, IIIa, IIIb, Iva, and IVb were assigned to 7.1, 36.1, 38.5, 9.8, 4.1, and 4.1% of the patients, respectively, with significant differences seen between the young and elderly patients (p < .05). In total, 52.5% of patients could eat normally, whereas 32.8% required a soft diet. Furthermore, 53.3 and 33.6% of patients achieved normal and intelligible speech, respectively. The aesthetic results were rated as excellent and good in 32.8 and 58.2% of patients, respectively. In total, 68.0% of the patients were alive and exhibited no evidence of disease, while 19.7% were alive with active disease. In addition, 12.3% of patients with stage III OTSCC died due to local recurrence or distant metastases. No differences in swallowing, speech, aesthetic, or survival outcomes were observed among the groups. Conclusions FSAIF is a simple, safe, and reliable method for reconstructing hemitongue defects following cancer ablation in young, middle-aged, and elderly patients with early and middle-stage OTSCC.